2013
DOI: 10.1136/bjophthalmol-2012-302218
|View full text |Cite
|
Sign up to set email alerts
|

Grey and white matter changes in children with monocular amblyopia: voxel-based morphometry and diffusion tensor imaging study

Abstract: In monocular amblyopia, cortices related to spatial vision underwent volume loss, which provided neuroanatomical evidence of stereoscopic defects. Additionally, white matter development was also hindered due to visual defects in amblyopes. Growth in the GMVs, WMVs and FA in the occipital lobe and precuneus may reflect a compensation effect by the unaffected eye in monocular amblyopia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 25 publications
3
38
0
1
Order By: Relevance
“…To study white matter volume changes, researchers have applied VBM to voxels that are classified as white matter and have found decreased volume in the white matter around the primary visual cortex, right premotor cortex, bilateral dorsolateral prefrontal cortex, bilateral cingulate cortex, and the bilateral optic radiations. 19,22,23 By contrast, increases in white matter volume have been reported in the bilateral cuneus areas and the right inferior frontal gyrus. 23 Diffusion tensor imaging, on the other hand, probes tissue properties at the micrometer scale within a magnetic resonance imaging (MRI) voxel by modeling movement of water molecules in multiple directions.…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…To study white matter volume changes, researchers have applied VBM to voxels that are classified as white matter and have found decreased volume in the white matter around the primary visual cortex, right premotor cortex, bilateral dorsolateral prefrontal cortex, bilateral cingulate cortex, and the bilateral optic radiations. 19,22,23 By contrast, increases in white matter volume have been reported in the bilateral cuneus areas and the right inferior frontal gyrus. 23 Diffusion tensor imaging, on the other hand, probes tissue properties at the micrometer scale within a magnetic resonance imaging (MRI) voxel by modeling movement of water molecules in multiple directions.…”
mentioning
confidence: 97%
“…19,22,23 By contrast, increases in white matter volume have been reported in the bilateral cuneus areas and the right inferior frontal gyrus. 23 Diffusion tensor imaging, on the other hand, probes tissue properties at the micrometer scale within a magnetic resonance imaging (MRI) voxel by modeling movement of water molecules in multiple directions. In white matter, where myelinated axons are directionally coherent, water molecules diffuse much more easily along the length of the axons than perpendicular to them.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Also the ADC values were increased in the postchiasmatic region in both groups of amblyopic patients. In two recent studies, DTI showed more voxels in the posterior parts of bilateral optic radiations of normal children than in the amblyopic children and authors suggested that this finding indicates that normal children have better development of the optic radiations [12][13][14][15]. Duan et al [16] recently reported that ADC values increased not only in occipital tracts such as the optic radiations but also in long-range association tracts connecting visual cortex to the frontal and temporal lobes and connecting the two hemispheres.…”
Section: Discussionmentioning
confidence: 95%